Scaling-up access to family planning may improve linear growth and child development in low and middle income countries. - Günther Fink; Christopher R Sudfeld; Goodarz Danaei; Majid Ezzati; Wafaie W Fawzi (PLoS ONE)
Background A large literature has indicated a robust association between birth spacing and child survival, but evidence on the association of birth timing with physical growth in low and middle income countries (LMICs) remains limited. Methods and results Data from 153 cross-sectional Demographic and Health Surveys (DHS) across 61 LMICs conducted between 1990 and 2011 were combined to assess the association of birth timing with child stunting (height-for-age z-score <-2). A total of 623,789 children of birth order 1-5 contributed to the maternal age analysis, while the birth spacing dataset consisted of 584,226 children of birth order 2 and higher. Compared to 27-34 year old mothers, maternal age under 18 years was associated with a relative stunting risk of 1.35 (95% CI: 1.29-1.40) for firstborn children, whereas the relative risk was 1.24 (95% CI: 1.19-1.29) for mothers aged 18-19 years. The association of young maternal age with stunting was significantly greater for urban residents and those in the top 50% of household wealth. Birth intervals less than 12 months and 12-23 months had relative risks for stunting of 1.09 (95% CI: 1.06-1.12) and 1.06 (95% CI: 1.05-1.06) as compared to a 24-35 month inter-pregnancy interval, respectively. The strength of both teenage pregnancy and short birth interval associations showed substantial variation across WHO region. We estimate that 8.6% (6.9-10.3%) of stunted cases in the South Asian DHS sample would have been averted by jointly eliminating teen pregnancies and birth intervals less than 24 months, while only 3.6% (1.5-5.7%) of stunting cases would have prevented in the Middle East and North Africa sample. Conclusions Postponing the age of first birth and increasing inter-pregnancy intervals has the potential to significantly reduce the prevalence of stunting and improve child development in LMICs.